Autoimmune thyroid disease and type 1 diabetes mellitus: same pathogenesis; new perspective?. (September 2020) - Li, Liyan; Liu, Shudong; Yu, Junxia
Autoimmune thyroid disease (AITD) and type 1 diabetes mellitus (T1DM) are two common autoimmune diseases that can occur concomitantly. In general, patients with diabetes have a high risk of AITD. It has been proposed that a complex genetic basis together with multiple nongenetic factors make a variable contribution to the pathogenesis of T1DM and AITD. In this paper, we summarize current knowledge in the field regarding potential pathogenic factors of T1DM and AITD, including human leukocyte antigen, autoimmune regulator, lymphoid protein tyrosine phosphatase, forkhead box protein P3, cytotoxic T lymphocyte-associated antigen, infection, vitamin D deficiency, and chemokine (C-X-C motif) ligand. These findings offer an insight into future immunotherapy for autoimmune diseases.